2018
DOI: 10.30880/ijscet.2018.09.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Management Approaches in Construction Supply Chain: A New Perspective of Stakeholder’s Theory

Abstract: Construction is dependent on accurate, timely and safe supply chain, otherwise whole project will be halted. Previously, it has found that most construction projects failed to complete on designated time that ultimately surges the cost as well. Although there are various approaches to deal with the situation, there is evidence that collaboration among stakeholders would reduce the risks and enhance the performance. Therefore, the aim of this study is to verify the relationship between the supply chain performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
15
0
4
Order By: Relevance
“…The treatment of employees with dignity, respect and sincerity affects employees' perceptions of interaction justice. Studies reveal that individuals consider the treatment they receive as an antecedent of their perceived justice (Shahbaz et al, 2018). Employees' perception of supervisors' behavior as fair during interpersonal interaction emerges as interactional justice.…”
Section: Interactional Justicementioning
confidence: 99%
“…The treatment of employees with dignity, respect and sincerity affects employees' perceptions of interaction justice. Studies reveal that individuals consider the treatment they receive as an antecedent of their perceived justice (Shahbaz et al, 2018). Employees' perception of supervisors' behavior as fair during interpersonal interaction emerges as interactional justice.…”
Section: Interactional Justicementioning
confidence: 99%
“…Huo, Zhao and Zhou, (2014) has studies IS with suppliers, customers and internal in Chines manufacturing and revealed that all have a positive effect on operational performance and internal IS also has a positive relationship with external IS. IS has a positive effect on operational performance but not significantly in the manufacturing sector of Turkey (Sezen, 2008;Shahbaz, Chandio, Oad, Ahmed,& Ullah, 2018). The today supply chain has become more fragile and risks have become a serious concern.…”
Section: Information Sharingmentioning
confidence: 99%
“…In this study, collaboration with external partners will be discussed. Shahbaz et al, [30] have revealed in many studies that in the current scenario, it is critical for companies to engage with external partners to address global challenges. The next section focuses on the further development of collaborative indicators after moderating collaborative approaches to sources of risk and performance.…”
Section: Collaborationmentioning
confidence: 99%